Proposing an architecture for developing tactical shooter games employing Virtual Reality - Barbosa, Ícaro S.; Vidal, Creto A.; C. Neto, Joaquim Bento; L. Júnior, Antônio José M.; Gomes, George Allan M. (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2023)
Tactical Shooters are a trendy subgenre within FPS games, focusing on realistic simulations of armed combat. With the advancement of Virtual Reality (VR) technology, which is becoming increasingly prevalent in household settings. In this article, we present an architecture that addresses the development of Tactical Shooters using Virtual Reality, aiming to provide players with enhanced immersion. To validate the proposed model, we developed two prototypes in which we analyzed the time and difficulty in developing them.